2022
DOI: 10.3390/ijms23137168
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Peptide Transporter 1 (TAP1) Promotes Resistance to MEK Inhibitors in Pancreatic Cancers

Abstract: Mitogen-activated protein kinase (MAPK) kinase (MEK) inhibitors show limited benefit in Kirsten rat sarcoma (KRAS) mutant pancreatic cancer due to drug resistance. To identify mechanisms of resistance to MEK inhibitor (MEKi), we employed a differential expression analysis of MEKi-sensitive versus MEKi-resistant KRAS-mutant pancreatic cancer cell lines. Here, we report that the antigen peptide transporter 1 (TAP1) expression levels of MEKi-resistant cell lines were notably higher than those of MEKi-sensitive ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In ACC and DLBC, the expression of SLC35C1 was positively correlated with TAP1. A previous study reported that TAP1 promoted chemoresistance by enhancing the transport of MEKi out of PDAC cells, leading to reduced intracellular MEKi concentration and attenuated inhibition of KRAS signaling pathways 30 . Therefore, SLC35C1 can be a potential target to provide a new strategy for the treatment of PDAC by interfering with TAP1.…”
Section: Discussionmentioning
confidence: 99%
“…In ACC and DLBC, the expression of SLC35C1 was positively correlated with TAP1. A previous study reported that TAP1 promoted chemoresistance by enhancing the transport of MEKi out of PDAC cells, leading to reduced intracellular MEKi concentration and attenuated inhibition of KRAS signaling pathways 30 . Therefore, SLC35C1 can be a potential target to provide a new strategy for the treatment of PDAC by interfering with TAP1.…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of TAP1 may be associated with the production of more tumor neoantigens, which in turn initiate tumor immunity ( 23 ). On the other hand, recently, researchers have illustrated that the silent TAP1 induced the presentation of a TAP-independent peptide in human tumor cells, and thereby enhanced the effectiveness of immune potentiating therapies ( 24 , 25 ), which is additionally considered associated with tumor drug resistance ( 26 28 ). Therefore, it is necessary to uncover the role of TAP1 in ccRCC.…”
Section: Introductionmentioning
confidence: 99%